Julia Kristeva Intertextual Reconfiguration of Interpretation of Rūḥ al-Qudus: An Analysis of Tafsīr ath-Ṭhabarī and al-Kabīr on Q.S. Al-Baqarah [2]:87 - Pratama, Masrul Maulana; Erawati, Desi; Faridatunnisa, Nor; Mualimin, Mualimin (Jurnal Ushuluddin, 2025)
This study is based on different interpretations of the concept of Rūḥ al-Qudus in classical and medieval exegesis. The aim of this study is to examine how this concept is presented in Tafsīr al-Ṭabarī and Tafsīr al-Rāzī and how Julia Kristeva's theory of intertextuality can illustrate the semantic relationships between the two. Through a qualitative-descriptive approach and an intertextual analysis of Jāmi‘ al-Bayān and al-Tafsīr al-Kabīr, this study concludes that al-Ṭabarī understands Rūḥ al-Qudus theocentrically and literally as the angel Jibrīl, i.e. as a divine mediator who acts as an enabler and bringer of revelations, based on the consensus of the traditions of the Companions and Tabi‘in. In contrast, al-Rāzī reinterprets this concept in a rational-philosophical manner, namely as quwwah rabbāniyyah, i.e. as a divine power that animates the spiritual consciousness ofhuman beings and enlivens their intellectual and moralcapacities. An intertextual analysis shows that al-Rāzī not onlyadopts al-Ṭabarī's view, but also undertakes a transformation ofmeaning through theological elaboration and metaphysicalspeculation, which expands the ontological position of Rūḥ al-Qudus in the discourse of revelation. This study contributes tointroducing the application of Kristeva's intertextuality model inexegesis and explaining the process of reconfiguring the meaningof Rūḥ al-Qudus in the intellectual dialogue between the classicaland medieval periods